The Selection Effects of Part-Time Work: Experimental Evidence from a Large-Scale Recruitment Drive - Kim, Hyuncheol Bryant; Kim, Hyunseob; Zhu, John Y. (The Review of Economics and Statistics, 2025)
We implement a field experiment to examine how part-time work attracts applicants with different productivity than full-time work. In a large-scale recruitment drive for a data-entry position in Ethiopia, either a part-time or full-time job opportunity was randomly offered. We find that part-time work attracts less qualified applicants with lower productivity but stronger preferences for short work hours. Our estimates show this selection effect may explain about half of the typical part-time wage penalty, which is about 25%. A simple model demonstrates how lack of high-quality workers with strong preference for short work hours could explain the experimental findings.